Biochemical and clinical characterization of metabolic phenotypes: a cross-sectional study from Maracaibo city, Venezuela [version 1; referees: awaiting peer review] (2018)
Background: In 1980, Reuben Andresen observed that in certain individuals, obesity did not increase mortality, introducing an atypical phenotype called “healthy obese”. Other studies reported that 10-15 % of lean individuals presented insulin resistance, hyperglycemia and dyslipidemia. The objective of this study was to evaluate biochemical and clinical characteristics of metabolic phenotypes in Maracaibo city. Methods: A descriptive, cross-sectional study with a randomized multistage sampling was performed including 1226 non diabetic individuals from both sexes. For phenotype definition, the subjects were first classified according to their BMI into Normal-Weight, Overweight and Obese; then divided in metabolically healthy and unhealthy using a two-step analysis cluster. To evaluate the relationship with coronary risk, a multiple logistic regression model was performed. Results: In the studied population, 5.2% (n=64) corresponded to unhealthy lean subjects, and 17.4% (n=217) to healthy obese subjects. Metabolically unhealthy normal-weight (MUNW) phenotype was found in males in 53.3% in contrast to 51.3% of metabolically unhealthy obese (MUO) phenotype found in females. An association between metabolically unhealthy phenotypes and a higher risk of a coronary event was found, especially for obese individuals (MHO: OR=1.85 CI95%: 1.11-3.09; p=0.02 and MUO: OR=2.09 CI95%: 1.34-3.28; p<0.01). Conclusion: Individuals with atypical metabolic phenotypes exist in Maracaibo city. Related factors may include insulin resistance, basal glucose levels, and triglycerides levels. Lastly, cardiovascular risk exhibited by healthy obese individuals should be classified in categories of major coronary risk related to lean subjects.